Problemas ambientales y sus efectos en el desarrollo agroturístico del Cantón Valencia, año 2019 - Briones Garcia, Gabriela Isabel (2020)
This research project was developed based on the problems evidenced in the canton of Valencia, Province of Los Rios, in terms of agrotourism and the impact generated by environmental problems in their development and growth, for which the respective framed objectives were established and supported by proper research and data collection for decision-making focused on solving all the problems found. In chapter 1, the research topics based on international, national, local and institutional contexts will be developed, raising the respective problematic citations, and in the same way the respective justification to plan the objectives that are sought to be achieved. Chapter 2, will contain the necessary theoretical support in the conceptual framework, referential and investigative antecedents attached to the subject under investigation, supported by reference of the most representative authors, all this research assembly to conclude with the hypotheses of the case. In Chapter 3, the results obtained from data collection, subsequent representation with the respective statistical tables and graphic representation will be announced. The respective proposal will be developed in Chapter 4, outlining the objectives that need to be achieved as part of the structure of the proposed alternative to solve the case, in addition to the respective conclusions and recommendations.